"Conventional" accounting vs "Islamic" accounting: the debate revisited. Issue 2 (2nd September 2014) - Velayutham, Sivakumar
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to evaluate the arguments that the assumptions underlying conventional accounting are incompatible with Islamic values, hence the need for new accounting objectives and assumptions. Design/methodology/approach – The paper adopts an analytic approach based on a combination of archival and bibliographic data sources. Findings – It is shown that this belief of incompatibility can be traced to misconceptions about the assumptions underlying "conventional accounting". It is then argued that the neglect of Islamic accounting in Islamic countries could be attributed to Islamic accounting not meeting the needs of users rather than acculturation or economic dependency. Research limitations/implications – The study relies solely on the literature and highlights important issues in the area but does not provide any empirical evidence. The implications are significant for the future development of Islamic accounting and the economies of Islamic countries. The objective of accounting is to provide useful information for economic decision-making and the adoption of wrong assumptions would limit the usefulness of accounting information. Originality/value – Few scholars have questioned the assumptions underlying Islamic accounting, and this debate is important for the continued development of Islamic accounting. The paper also attempts to contribute to the debate on the poor adoption of Islamic accounting.